Religious Youth Engagement in Biodiversity Protection: A Mixed-Methods Study on Faith-Based Environmental Programs - Hari Imbrani; Dina Yulia Wijaya; Acim Acim; Emad Amkhatirah (Green Philosophy: International Journal of Religious Education and Philosophy, 2025)
This study explores the role of faith-based environmental programs in fostering youth engagement in biodiversity protection. As global biodiversity continues to decline, there is an increasing recognition of the importance of engaging young people in conservation efforts. Faith-based organizations (FBOs) have the potential to play a significant role in this effort, leveraging religious teachings and values to inspire environmental stewardship. The study uses a mixed-methods approach, including surveys, focus group discussions, and case studies, to examine how faith-based programs influence youth involvement in activities such as community gardens, reforestation efforts, and species protection projects. The findings suggest that faith-based programs are effective in nurturing long-term engagement in biodiversity protection by instilling values of responsibility and stewardship. Spiritual motivations, community support, and educational mentorship emerge as key factors contributing to sustained youth participation in conservation initiatives. However, challenges such as limited resources, generational differences in ecological engagement, and the integration of doctrinal teachings with scientific conservation practices are identified. The study concludes that faith-based environmental programs can expand their impact by integrating environmental education into their existing frameworks, fostering partnerships with environmental organizations, and creating inclusive platforms for all youth groups. Further research is needed to explore the long-term impact of faith-based programs on youth engagement and biodiversity protection, and to identify strategies for optimizing these programs for greater effectiveness.